Addressing the Aging Workforce Crisis Through Intergenerational Programming: A Retrospective Analysis of Perfect Pair. - Manocha, Samiya; Lerner, Emily Theresa; Rueppel, Elizabeth; Casey, Kamryn; Karmarkar, Shriya; Lerner, Edie Julia; Zietlow, Kahli (Journal of the American Geriatrics Society, 2026)
Background: The growing older adult population in the United States creates a demand for professionals in the field of aging, though this remains a space that is overlooked by young adults beginning their career exploration. Perfect Pair is a nonprofit organization that connects older adults with college students to foster intergenerational connections. In this retrospective study, we assessed the impact that participation in Perfect Pair's programming had on college students' interest in working in the aging field as a future career. Participants and Setting: Study participants included current and past college student participants of the Perfect Pair program across 17 college chapters. Methods: We administered a retrospective survey that assessed participants' attitudes toward a career in aging. Survey questions included pre‐post and post‐program questions assessed by a Likert scale, and data was analyzed by non‐parametric statistical analysis. Results: The survey was completed by 100 participants, a response rate of 10.1%. We found statistically significant differences between general members and students who engaged more with the program, such as "matched" members who met weekly with an older adult and executive board members who led their college chapter. Members that were more involved showed higher perceived preparedness to work with older adults in the future (p < 0.001) and engagement with issues associated with aging (p = 0.002). Overall, all members of the program reported an increase in their interest in working with older adults after participating in Perfect Pair (p < 0.001). This is corroborated by narrative responses, where students share excitement to pursue a career in aging. Conclusion: Perfect Pair encourages and prepares college students to pursue a career in aging and engages them in issues associated with aging. This has strong implications for future intergenerational programming that aims to promote workforce development in the aging space. Summary: Key points ○College students participating in Perfect Pair, a national intergenerational volunteer program connecting students with older adults, showed an increase in interest in careers in aging, with overall participants rising from 37% to 58% reporting high interest in working with older adults.○Students with greater program engagement, particularly in those matched weekly with older adults and college chapter executive board members, demonstrated significantly higher levels of career preparedness and engagement with aging issues compared to less involved participants, suggesting a dose–response relationship.○Among program alumni currently working in the workforce, 80% work with older adults in some capacity, demonstrating real‐world career impact beyond student‐stated intentions.Why does this paper matter? ○With widespread workforce shortages across aging‐related fields, Perfect Pair provides evidence that structured intergenerational programming during undergraduate education can effectively cultivate the next generation of aging professionals. This model offers a scalable solution to address the growing demand for professionals trained to care for our rapidly aging population.